Look After Your Heart programme: impact on health status, exercise knowledge, attitudes, and behaviour of retired women in England. Issue 2 (April 1994) - Rowland, L; Dickinson, E J; Newman, P; Ford, D; Ebrahim, S
Abstract : OBJECTIVES–To evaluate the impact of the Health Education Authority's 20 hour Look After Your Heart health promotion course on a large group of retired women. DESIGN–Three groups of retired women were compared: group 1 women, drawn from 12 retirement groups, participated in the programme; group 2, drawn randomly from the same groups, declined; group 3, selected randomly from 12 different retirement groups matched for geographical area, were not offered the course. SETTING–Twenty four retirement groups established by a major national retail company in England. SUBJECTS–A total of 739 women with a mean age of 66 years participated. Altogether 200 women were in group 1, 192 in group 2, and 347 in group 3. MAIN OUTCOME MEASURE–The Nottingham Health Profile was administered and exercise knowledge, attitudes, and behaviour of the three groups were assessed using a validated, reliable questionnaire. RESULTS–Group 1 had significantly better self-perceived health, indicated by lower Nottingham Health Profile scores, more exercise knowledge, and positive exercise attitudes and they did more exercise than the other two groups. The responses of groups 2 and 3 were similar. Time since completion of the programme did not have any effect on Nottingham Health Profile scores, exercise knowledge, and behaviour. CONCLUSION–The Look After Your Heart programme is associated with beneficial and persistent effects in retired women. Detailed studies are needed to confirm whether these associations are due to the programme or reflect the selection of fitter, healthier subjects.